2005
DOI: 10.1096/fj.04-2532fje
|View full text |Cite
|
Sign up to set email alerts
|

C1‐TEN is a negative regulator of the Akt/PKB signal transduction pathway and inhibits cell survival, proliferation, and migration

Abstract: We have previously identified C1 domain-containing phosphatase and TENsin homologue (C1-TEN) as being an intracellular binding partner for Axl receptor tyrosine kinase (RTK). C1-TEN is a tensin-related protein that houses an N-terminal region with predicted structural similarity to PTEN. Here, we report our observations on the effects of ectopic expression of C1-TEN in HEK293 cells, which resulted in profound molecular and phenotypic changes. Stable expression of C1-TEN altered cellular morphology, with less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 26 publications
4
92
0
Order By: Relevance
“…A second phosphorylation-mediated mechanism of receptor downregulation is receptor dephosphorylation by protein tyrosine phosphatases. The putative tyrosine phosphatase C1-TEN has been shown to bind Axl and overexpression of C1-TEN correlates with reduced cell survival, proliferation, and migration of 293 cells (Hafizi et al, 2002(Hafizi et al, , 2005b. Although neither enzymatic activity of C1-TEN nor direct dephosphorylation of Axl have been demonstrated, these results are consistent with C1-TEN-mediated Axl inactivation.…”
Section: Mechanisms Of Deactivation-cellularmentioning
confidence: 89%
“…A second phosphorylation-mediated mechanism of receptor downregulation is receptor dephosphorylation by protein tyrosine phosphatases. The putative tyrosine phosphatase C1-TEN has been shown to bind Axl and overexpression of C1-TEN correlates with reduced cell survival, proliferation, and migration of 293 cells (Hafizi et al, 2002(Hafizi et al, , 2005b. Although neither enzymatic activity of C1-TEN nor direct dephosphorylation of Axl have been demonstrated, these results are consistent with C1-TEN-mediated Axl inactivation.…”
Section: Mechanisms Of Deactivation-cellularmentioning
confidence: 89%
“…PI3K induces Akt phosphorylation/activation, whereas PTEN inhibits Akt activation through the dephosphorylation of phosphatidylinositol-3,4,5-triphosphate, which is generated from phosphatidylinositol-4,5-bisphosphate by PI3K [2,4,11]. Negative regulators, such as C1 domain-containing PTEN, carboxy-terminal modulator protein, Trb3, and Keratin K10, are also reported to inactivate Akt [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…PDK1 phosphorylates Akt at Thr 308 , which causes a charge-induced conformational change, allowing Akt for substrate binding and an increased rate of catalysis. Akt is further activated by the phosphorylation of Ser 473 , which can be catalyzed by various kinases, including PDK2, DNA-PK, mammalian target of rapamysin, rictor complex, integrin linked kinase, and protein kinase C␤II (Feng et al, 2004;Kawakami et al, 2004;Fayard et al, 2005;Sarbassov et al, 2005 It has been demonstrated that PI3K plays an essential role in the epidermal growth factor (EGF)-induced membrane protrusion by regulating not only Akt (Higuchi et al, 2001;Nishita et al, 2004;Hafizi et al, 2005) but also Rac and Ral GTPases (Tian et al, 2002;Gavard et al, 2004;Nishita et al, 2004;Takaya et al, 2004). However, the mechanism by which Akt regulates the cytoskeletal remodeling and the relationship to Ral and Rac has been still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that PI3K plays an essential role in the epidermal growth factor (EGF)-induced membrane protrusion by regulating not only Akt (Higuchi et al, 2001;Nishita et al, 2004;Hafizi et al, 2005) but also Rac and Ral GTPases (Tian et al, 2002;Gavard et al, 2004;Nishita et al, 2004;Takaya et al, 2004). However, the mechanism by which Akt regulates the cytoskeletal remodeling and the relationship to Ral and Rac has been still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation